Systemic delivery of proresolving lipid mediators resolvin D2 and maresin 1 attenuates intimal hyperplasia in mice. Issue 6 (16th March 2015) - Akagi, Daisuke; Chen, Mian; Toy, Robert; Chatterjee, Anuran; Conte, Michael S.
ABSTRACT: Vascular injury induces a potent inflammatory response that influences vessel remodeling and patency, limiting long‐term benefits of cardiovascular interventions such as angioplasty. Specialized proresolving lipid mediators (SPMs) derived from ω‐3 polyunsaturated fatty acids [eicosapentaenoic acid and docosahexaenoic acid (DHA)] orchestrate resolution in diverse settings of acute inflammation. We hypothesized that systemic administration of DHA‐derived SPMs [resolvin D2 (RvD2) and maresin 1 (MaR1)] would influence vessel remodeling in a mouse model of arterial neointima formation (carotid ligation). In vitro, SPM treatment inhibited mouse aortic smooth muscle cell migration (IC50 ≅ 1 nM) to a PDGF gradient and reduced TNF‐α‐stimulated p65 translocation, superoxide production, and proinflammatory gene expression (MCP‐1). In vivo, adult FVB mice underwent unilateral carotid artery ligation with administration of RvD2, MaR1, or vehicle (100 ng by intraperitoneal injection at 0, 1, 3, 5, and 7 d after ligation). In ligated carotid arteries at 4 d, SPM treatment was associated with reduced cell proliferation and neutrophil and macrophage recruitment and increased polarization of M2 macrophages in the arterial wall. Neointimal hyperplasia (at 14 d) was notably attenuated in RvD2 (62%)‐ and MaR1 (67%)‐treated mice, respectively. Modulation of resolution pathways may offer new opportunities to regulate the vascular injury response and promote vascular homeostasis.—Akagi, D., Chen, M., Toy, R., Chatterjee, A., Conte, M. S. Systemic delivery of proresolving lipid mediators resolvin D2 and maresin 1 attenuates intimal hyperplasia in mice. FASEB J. 29, 2504‐2513 (2015). www.fasebj.org